Synthesis of palmyrolide A and its cis-isomer and mechanistic insight into trans-cis isomerisation of the enamide macrocycle - Philkhana, Satish Chandra; Seetharamsingh, B.; Dangat, Yuvraj B.; Vanka, Kumar; Reddy, D. Srinivasa (Chemical Communications, 2013)
Concise and protecting-group free synthesis of ent-palmyrolide A and (-)-cis-palmyrolide A were achieved starting from commercially available (S)-citronellal. The key fragment of palmyrolide A, ``(5S,7S)-7-hydroxy-5,8,8-trimethylnonanamide'', which makes up the most challenging part of the target molecule, was prepared in just three steps. A plausible mechanism for the trans-cis isomerization of the double bond in the macrocycle has been investigated.